Expression analysis elucidates the roles of Nicastrin, Notch4, and Hes1 in prognosis and endocrine-therapy resistance in ER-positive breast cancer patients - Arad Boustan; Rosa Jahangiri; Asefeh Dahmardeh Ghalehno; Mahdieh Khorsandi; Fatemeh Mosaffa; Khadijeh Jamialahmadi (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Although some proposed mechanisms responsible for tamoxifen resistance have already been present, further study is needed to determine the mechanisms underlying tamoxifen resistance more clearly. The critical role of Notch signaling has been described in promoting resistance in therapeutics, but there is little information about its role in tamoxifen resistance progression. Experimental approach: In the present study, the expression of Notch pathway genes, including Notch4, nicastrin and the Notch downstream target Hes1 was evaluated using quantitative RT-PCR in 36 tamoxifen-resistant (TAM-R) and 36 tamoxifen-sensitive (TAM-S) patients. Expression data were correlated with the clinical outcome and survival of patients. Findings/Results: mRNA levels of Notch4 (fold change = 2.7), nicastrin (fold change = 6.71), and Hes1 (fold change= 7.07) were significantly higher in TAM-R breast carcinoma patients compared to sensitive cases. We confirmed all these genes were co-expressed. Hence, it seems that Notch signaling is involved in tamoxifen resistance in our TAM-R patients. Obtained results showed that Hes1, nicastrin, and Notch4 mRNA upregulation was correlated with the N stage. The extracapsular nodal extension was associated with nicastrin and Notch4 overexpression. Moreover, nicastrin overexpression was correlated with perineural invasion. Hes1 upregulation was also associated with nipple involvement. Finally, the Cox regression proportional hazard test revealed that overexpression of nicastrin was an independent worse survival factor. Conclusion and implications: Presumably, upregulation of the Notch pathway may be involved in tamoxifen resistance in breast cancer patients.